Pre-treatment of rice husks for fungal fermentation - Ang, T.N.; Ngoh, G.C.; Chua, A.S.M. (2009)
Agro by-products can be sustainable feedstock for the production of various versatile bio-products. The pre- treatment of which is needed for optimal utilization of recalcitrant lignocellulosic biomass. This study investigated the effect of various acids and alkalis on the pre-treatment of rice husks to make it suitable for use in fermentation. Dry rice husks with the weight of 10 g were pre-treated with 1 % (w/v) of five acids and two alkalis with water loading of 10 ml/g of rice husks. The rice husks that was pre-treated with 1 % (w/v) nitric acid produced the highest total reducing sugars in the hydrolyzate (approximately 4.2 mg/ g of rice husks) after 8 hours at 100 oC followed by pre-treatment with acetic acid (~0.7 mg) and sodium hydroxide (~0.4 mg). Hydrolysis with other acids and alkali produced less than 0.1 mg reducing sugars/ g rice husks. In conclusion, nitric acid was found to be the best hydrolyzing reagent for pre-treatment of rice husks in this study.